Preparation method and application of atomic-scale dispersion high-entropy metal doped carbon electrocatalyst
Through the preparation method of atomic-level dispersed high entropy metal-doped carbon electrocatalyst, the problem of high cost of existing platinum-based electrocatalysts is solved, high oxygen reduction activity and durability are achieved, and the performance and efficiency of PEMFC are improved.
Patent Information
- Application Number
- CN202411749505.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-18
AI Technical Summary
The existing platinum-based electrocatalysts are costly, limiting the widespread application of polymer electrolyte membrane fuel cells (PEMFCs), and it is necessary to develop low-cost, high-efficiency and high-stability non-precious metal electrocatalysts.
Using the preparation method of atomically dispersed high-entropy metal-doped carbon electrocatalyst, a hybrid precursor is formed by mixing the porphyrin mixture with zinc brine solution under specific conditions, and pyrolyzed at high temperature to obtain an atomically dispersed high-entropy metal-doped carbon electrocatalyst.
High oxygen reduction activity and durability are achieved, the half-wave potential is significantly improved, and the high entropy structure of the material ensures the uniform distribution and synergy of various metal elements, improving electrocatalytic performance.
Smart Images

Figure HDA0005164640820000011 
Figure HDA0005164640820000012 
Figure HDA0005164640820000021
Abstract
Description
Technical Field
[0001] The present invention relates to an electrocatalyst, and in particular to a preparation method and application of an atomic-level dispersed high-entropy metal-doped carbon electrocatalyst. Background Art
[0002] Today's society is facing the contradiction between economic development and the shortage of fossil energy and serious environmental pollution. Therefore, it is urgent to adopt efficient and clean energy technologies to solve this problem. Polymer electrolyte membrane fuel cells (PEMFC) have attracted widespread attention due to their high power density, fast start-up, and environmental friendliness. Platinum-based electrocatalysts are one of the core materials of PEMFC, but the large amount of platinum-based materials and their high price limit the widespread application of PEMFC. One of the solutions is to develop low-cost, high-efficiency and high-stability non-precious metal electrocatalysts to replace platinum-based electrocatalysts to promote the commercialization of PEMFC. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide an electrocatalyst with high oxygen reduction activity.
[0004] The present invention provides a method for preparing an atomically dispersed high-entropy metal-doped carbon electrocatalyst. The preparation method comprises the following steps: dissolving a porphyrin mixture in an aqueous solution of a nitrogen-containing ligand to obtain a solution A; mixing a zinc salt aqueous solution with the solution A to obtain a hybrid precursor; and pyrolyzing the hybrid precursor under an inert atmosphere to obtain an atomically dispersed high-entropy metal-doped carbon electrocatalyst.
[0005] Furthermore, the porphyrin mixture is manganese-containing porphyrin, iron-containing porphyrin, cobalt-containing porphyrin, nickel-containing porphyrin and copper-containing porphyrin, and the concentration of each metal porphyrin in the porphyrin mixture is 0.1-0.5M and the molar number of each metal porphyrin is equal.
[0006] Further, the porphyrin mixture is a mixture of 5,10,15,20-tetrakis(4-carboxyphenyl)manganeseporphyrin, 5,10,15,20-tetrakis(4-carboxyphenyl)ironporphyrin, 5,10,15,20-tetrakis(4-carboxyphenyl)cobaltporphyrin, 5,10,15,20-tetrakis(4-carboxyphenyl)nickelporphyrin and 5,10,15,20-tetrakis(4-carboxyphenyl)copperporphyrin, or a mixture of protoporphyrin manganese chloride, hemin, protoporphyrin cobalt chloride, protoporphyrin nickel chloride and protoporphyrin copper chloride.
[0007] Furthermore, the nitrogen-containing ligand is one or more of 1-methylimidazole, 2-ethylimidazole, 4-methylimidazole, 2-ethyl-4-methylimidazole, 4(5)-(hydroxymethyl)imidazole, and 4-nitro-5-methylimidazole, and the concentration of the nitrogen-containing ligand is 5-20M.
[0008] Furthermore, the zinc salt is one of zinc acetate, zinc sulfate, zinc chloride and zinc nitrate, and the concentration of the zinc salt is 0.5-2.0M.
[0009] Furthermore, the volume ratio of solution A to the zinc salt aqueous solution is 1:1.
[0010] Furthermore, the pyrolysis condition is 900-1000° C. for 2-4 hours.
[0011] Another object of the present invention is to provide an atomically dispersed high entropy metal-doped carbon electrocatalyst prepared by the above preparation method.
[0012] Another object of the present invention is to provide an application of the above-mentioned atomically dispersed high entropy metal-doped carbon electrocatalyst in a polymer electrolyte membrane fuel cell.
[0013] The beneficial effects of the present invention are:
[0014] The electrocatalyst prepared by the present invention contains multiple metal elements with similar contents and is evenly dispersed in a carbon matrix at the atomic level, similar to a high-entropy single-atom catalyst. Its electrocatalytic oxygen reduction activity and durability are much higher than those of a low-entropy single-atom catalyst. The high oxygen reduction active site density and the synergistic effect between different metals promote the improvement of oxygen reduction activity and durability.
[0015] The preparation method of the invention makes full use of the interaction between the peripheral groups of the metal porphyrin and the imidazole ligand and the metal ion, that is, the porphyrin molecules with carboxyl functional groups have hydrogen bonding with the water-soluble imidazole ligand and can coordinate with the metal zinc ion at the same time, and the self-assembly interaction between the metal porphyrin molecules with the same functional group and the same ligand and metal ion is balanced, so that a variety of metal porphyrins can be stably, uniformly and approximately equal in amount in the hybrid precursor, and are not easy to fall off and aggregate, so as to form a high-entropy hybrid precursor, and a high-entropy carbon electrocatalyst doped with a variety of metal atoms is formed after high-temperature pyrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The present invention is attached Figure 7 width,
[0017] Figure 1 This is a transmission electron microscope (TEM) image of the hybrid precursor FeCoCuMnNi-LC obtained in Example 1;
[0018] Figure 2 The X-ray diffraction (XRD) pattern of the atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H obtained in Example 1;
[0019] Figure 3The high-angle dark field scanning transmission electron microscopy (HAADF-STEM) and corresponding element distribution (STEM-EDS) images of the atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H obtained in Example 1;
[0020] Figure 4 The oxygen reduction polarization curves of the atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H obtained in Example 1 under acidic and alkaline conditions;
[0021] Figure 5 The oxygen reduction polarization curves of the atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H obtained in Example 1 before and after the durability test under acidic and alkaline conditions;
[0022] Figure 6 TEM image of the electrocatalyst FeCoCuMnNi@C1-H obtained in Comparative Example 1;
[0023] Figure 7 This is a comparison chart of the oxygen reduction (ORR) activity of the electrocatalysts obtained in Comparative Example 2 and Example 1. DETAILED DESCRIPTION
[0024] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0025] Example 1
[0026] A mixture of 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)manganese porphyrin, 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)iron porphyrin, 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)cobalt porphyrin, 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)nickel porphyrin, and 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)copper porphyrin was dissolved in 10 mL of 10 M 1-methylimidazole was added to an aqueous solution to obtain solution A; 1.0 M zinc chloride was dissolved in 10 mL deionized water to obtain solution B; solution B was slowly added dropwise to the continuously stirred solution A, stirred for 4 h, filtered to obtain a precipitate, and dried at 80 ° C for 12 h to obtain a hybrid precursor FeCoCuMnNi-LC; the hybrid precursor FeCoCuMnNi-LC was pyrolyzed at 900 ° C for 2 h in an Ar atmosphere to obtain an atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H.
[0027] like Figure 1 As shown, TEM results show that the prepared hybrid precursor FeCoCuMnNi-LC is granular.
[0028] Table 1 shows the ICP results of the prepared atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H.
[0029] Table 1
[0030] project element Mass fraction (%) 1 Fe 0.8 2 Co 0.7 3 Ni 0.6 4 Mn 0.6 5 Cu 0.4
[0031] Conclusion: As shown in Table 1, the ICP results show that the contents of each metal element are similar, which has a high entropy effect, making the material have higher configurational entropy and structural stability, which is beneficial to the improvement of oxygen reduction performance.
[0032] like Figure 2 As shown, the XRD results show that the prepared atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H has an amorphous carbon structure and does not contain metal-based nanoparticles.
[0033] like Figure 3 As shown, HAADF-STEM and corresponding mapping results indicate that no metal clusters or nanoparticles are generated in the atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H, and that Fe, Co, Ni, Mn, Cu, and N elements are uniformly distributed in the carbon matrix, which is an atomically dispersed high entropy metal-doped amorphous carbon structure.
[0034] In an O2-saturated 0.1M KOH solution, the oxygen reduction polarization curve was tested with a scanning voltage range of 0-1.2V (vs. RHE), Hg / HgO as the reference electrode, glassy carbon as the working electrode, and graphite rod as the counter electrode. The results are shown in Figure 4 The results show that the prepared atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H has excellent oxygen reduction activity in alkaline media, with a half-wave potential of 0.917V (vs.RHE). In an O2-saturated 0.1M HClO4 solution, the oxygen reduction polarization curve was tested with a scanning voltage range of 0-1.2V (vs.RHE), Hg / Hg2Cl2 as the reference electrode, glassy carbon as the working electrode, and graphite rod as the counter electrode. The results are shown in Figure 4 The results showed that the prepared atomically dispersed high-entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H has excellent oxygen reduction activity in acidic medium with a half-wave potential of 0.823 V (vs. RHE).
[0035] In an O2-saturated 0.1M KOH solution, the oxygen reduction polarization curve was tested with a scanning voltage range of 0-1.2V (vs. RHE), Hg / HgO as the reference electrode, glassy carbon as the working electrode, and graphite rod as the counter electrode. The results are shown in Figure 5The results show that the prepared atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H has excellent durability in alkaline media, and the half-wave potential only decays by 10mV after 3000 cycles of dynamic potential scanning. In an O2-saturated 0.1M HClO4 solution, the oxygen reduction polarization curve was tested with a scanning voltage range of 0-1.2V (vs.RHE), Hg / Hg2Cl2 as the reference electrode, glassy carbon as the working electrode, and graphite rod as the counter electrode. The results are shown in Figure 5 The results showed that the prepared atomically dispersed high-entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H had excellent durability in acidic media, and the half-wave potential only decayed by 12 mV after 3000 cycles of dynamic potential scanning.
[0036] Example 2
[0037] A mixture of 0.1 M 5,10,15,20-tetrakis(4-carboxyphenyl)manganese porphyrin, 0.1 M 5,10,15,20-tetrakis(4-carboxyphenyl)iron porphyrin, 0.1 M 5,10,15,20-tetrakis(4-carboxyphenyl)cobalt porphyrin, 0.1 M 5,10,15,20-tetrakis(4-carboxyphenyl)nickel porphyrin, and 0.1 M 5,10,15,20-tetrakis(4-carboxyphenyl)copper porphyrin was dissolved in 10 mL of 10 M 1-methylimidazole was added to an aqueous solution to obtain solution A; 1.0 M zinc chloride was dissolved in 10 mL deionized water to obtain solution B; solution B was slowly added dropwise to the continuously stirred solution A, stirred for 4 h, filtered to obtain a precipitate, and dried at 80 ° C for 12 h to obtain a hybrid precursor FeCoCuMnNi-LC; the hybrid precursor FeCoCuMnNi-LC was pyrolyzed at 900 ° C for 2 h in an Ar atmosphere to obtain an atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H1.
[0038] Example 3
[0039] A mixture of 0.5M protoporphyrin manganese chloride, 0.5M hemin, 0.5M protoporphyrin cobalt chloride, 0.5M protoporphyrin nickel chloride and 0.5M protoporphyrin copper chloride was dissolved in 10mL 10M 1-methylimidazole aqueous solution to obtain solution A; 1.0M zinc chloride was dissolved in 10mL deionized water to obtain solution B; solution B was slowly added dropwise to the continuously stirred solution A, stirred for 4h, filtered to obtain a precipitate, and dried at 80°C for 12h to obtain a hybrid precursor FeCoCuMnNi-LC; the hybrid precursor FeCoCuMnNi-LC was pyrolyzed at 900°C for 2h under Ar atmosphere to obtain an atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H2.
[0040] Example 4
[0041] A mixture of 0.2M protoporphyrin manganese chloride, 0.2M hemin, 0.2M protoporphyrin cobalt chloride, 0.2M protoporphyrin nickel chloride and 0.2M protoporphyrin copper chloride was dissolved in 10mL of 10M 4-nitro-5-methylimidazole aqueous solution to obtain solution A; 1.0M zinc chloride was dissolved in 10mL of deionized water to obtain solution B; solution B was slowly added dropwise to the continuously stirred solution A, stirred for 4h, filtered to obtain a precipitate, and dried at 80°C for 12h to obtain a hybrid precursor FeCoCuMnNi-LC; the hybrid precursor FeCoCuMnNi-LC was pyrolyzed at 900°C for 2h under Ar atmosphere to obtain an atomically dispersed high entropy metal-doped carbon electrocatalyst FeCoCuMnNi-LC-H3.
[0042] Comparative Example 1 (high concentration porphyrin)
[0043] A mixture of 1.0 M 5,10,15,20-tetrakis(4-carboxyphenyl)manganese porphyrin, 1.0 M 5,10,15,20-tetrakis(4-carboxyphenyl)iron porphyrin, 1.0 M 5,10,15,20-tetrakis(4-carboxyphenyl)cobalt porphyrin, 1.0 M 5,10,15,20-tetrakis(4-carboxyphenyl)nickel porphyrin, and 1.0 M 5,10,15,20-tetrakis(4-carboxyphenyl)copper porphyrin was dissolved in 10 mL of 10 M Solution A was obtained by dissolving 1.0 M zinc chloride in 10 mL deionized water. Solution B was obtained by slowly dropping solution B into the continuously stirred solution A and stirring for 4 h. The precipitate was filtered and dried at 80 °C for 12 h to obtain a hybrid precursor FeCoCuMnNi-LC. The hybrid precursor FeCoCuMnNi-LC was pyrolyzed at 900 °C for 2 h under Ar atmosphere to obtain the electrocatalyst FeCoCuMnNi@C1-H.
[0044] like Figure 6 As shown, TEM results indicate that the prepared electrocatalyst FeCoCuMnNi@C1-H contains a large amount of metal-based nanoparticles and does not form an atomically dispersed metal-doped carbon structure.
[0045] Comparative Example 2 (less than 5 types of porphyrins)
[0046] A mixture of 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)ironporphyrin, 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)cobaltporphyrin, 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)nickelporphyrin, and 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)copperporphyrin was dissolved in 10 mL of 10 M Solution A was obtained by dissolving 1.0 M zinc chloride in 10 mL deionized water. Solution B was slowly added dropwise to the stirring solution A, stirred for 4 h, filtered to obtain a precipitate, and dried at 80 ° C for 12 h to obtain a hybrid precursor FeCoCuMnNi@C2. The hybrid precursor FeCoCuMnNi@C2 was pyrolyzed at 900 ° C for 2 h in an Ar atmosphere to obtain an electrocatalyst FeCoCuNi@C2-H.
[0047] In an O2-saturated 0.1M KOH solution, the oxygen reduction polarization curve was tested with a scanning voltage range of 0-1.2V (vs. RHE), Hg / HgO as the reference electrode, glassy carbon as the working electrode, and graphite rod as the counter electrode. The results are shown in Figure 7 The results show that the half-wave potential of the prepared electrocatalyst FeCoCuNi@C2-H in alkaline medium is 0.876V (vs. RHE), which is 41mV lower than that in Example 1. In an O2-saturated 0.1M HClO4 solution, the oxygen reduction polarization curve was tested with a scanning voltage range of 0-1.2V (vs. RHE), Hg / Hg2Cl2 as the reference electrode, glassy carbon as the working electrode, and graphite rod as the counter electrode. The results are shown in Figure 7 The results show that the half-wave potential of the prepared electrocatalyst FeCoCuNi@C2-H in acidic medium is 0.765V (vs.RHE), which is 58mV lower than that in Example 1.
[0048] Comparative Example 3 (Different Metal Salts)
[0049] A mixture of 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)manganese porphyrin, 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)iron porphyrin, 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)cobalt porphyrin, 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)nickel porphyrin, and 0.5 M 5,10,15,20-tetrakis(4-carboxyphenyl)copper porphyrin was dissolved in 10 mL of 10 M Solution A was obtained by dissolving 1.0 M cobalt chloride in 10 mL deionized water. Solution B was slowly added dropwise to the stirring solution A, stirred for 4 h, filtered to obtain a precipitate, and dried at 80 °C for 12 h to obtain a hybrid precursor FeCoCuMnNi@C3. The hybrid precursor FeCoCuMnNi@C3 was pyrolyzed at 900 °C for 2 h under Ar atmosphere to obtain the electrocatalyst FeCoCuMnNi@C3-H.
[0050] The pore structure of the formed electrocatalyst FeCoCuMnNi@C3-H has changed, and a large number of pores that are conducive to the reaction are not formed, resulting in low activity.
Claims
1. A method for preparing an atomically dispersed high entropy metal-doped carbon electrocatalyst, characterized in that: The preparation method comprises the following steps: dissolving the porphyrin mixture in an aqueous solution of a nitrogen-containing ligand to obtain a solution A; mixing the zinc salt aqueous solution with solution A to obtain a hybrid precursor; The hybrid precursor is pyrolyzed under an inert atmosphere to obtain atomically dispersed high-entropy metal-doped carbon electrocatalysts.
2. The preparation method according to claim 1, characterized in that: The porphyrin mixture comprises manganese-containing porphyrin, iron-containing porphyrin, cobalt-containing porphyrin, nickel-containing porphyrin and copper-containing porphyrin. The concentration of each metal porphyrin in the porphyrin mixture is 0.1-0.5M and the molar number of each metal porphyrin is equal.
3. The preparation method according to claim 2, characterized in that: The porphyrin mixture is a mixture of 5,10,15,20-tetrakis(4-carboxyphenyl)manganese porphyrin, 5,10,15,20-tetrakis(4-carboxyphenyl)iron porphyrin, 5,10,15,20-tetrakis(4-carboxyphenyl)cobalt porphyrin, 5,10,15,20-tetrakis(4-carboxyphenyl)nickel porphyrin and 5,10,15,20-tetrakis(4-carboxyphenyl)copper porphyrin, or a mixture of protoporphyrin manganese chloride, hemin, protoporphyrin cobalt chloride, protoporphyrin nickel chloride and protoporphyrin copper chloride.
4. The preparation method according to claim 1, characterized in that: The nitrogen-containing ligand is one or more of 1-methylimidazole, 2-ethylimidazole, 4-methylimidazole, 2-ethyl-4-methylimidazole, 4(5)-(hydroxymethyl)imidazole, and 4-nitro-5-methylimidazole, and the concentration of the nitrogen-containing ligand is 5-20M.
5. The preparation method according to claim 1, characterized in that: The zinc salt is one of zinc acetate, zinc sulfate, zinc chloride and zinc nitrate, and the concentration of the zinc salt is 0.5-2.0M.
6. The preparation method according to claim 1, characterized in that: The volume ratio of solution A to the zinc salt aqueous solution is 1:
1.
7. The preparation method according to claim 1, characterized in that: The pyrolysis condition is 900-1000° C. for 2-4 hours.
8. An atomically dispersed high entropy metal-doped carbon electrocatalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the atomically dispersed high entropy metal-doped carbon electrocatalyst according to claim 8 in polymer electrolyte membrane fuel cells.